2023
DOI: 10.5808/gi.23038
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming taxonomic challenges in DNA barcoding for improvement of identification and preservation of clariid catfish species

Piangjai Chalermwong,
Thitipong Panthum,
Pish Wattanadilokcahtkun
et al.

Abstract: DNA barcoding without assessing reliability and validity causes taxonomic errors of species identification, which is responsible for disruptions of their conservation and aquaculture industry. Although DNA barcoding facilitates molecular identification and phylogenetic analysis of species, its availability in clariid catfish lineage remains uncertain. In this study, DNA barcoding was developed and validated for clariid catfish. 2,970 barcode sequences from mitochondrial cytochrome c oxidase I (COI) and cytochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…This suggests that the SBR-KSN and NYK populations were derived from distinct lineages. Chalermwong et al [ 73 ] asserted that a species complex was identified within the North African catfish, which was characterized by substantial intraspecific sequence divergence, although it was classified under the same species using a species delimitation approach based on DNA barcodes. Moreover, ZZ/ZW sex determination system, which is likely the ancestral system for the North African catfish, is the same as the systems reported in Africa and Israel.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the SBR-KSN and NYK populations were derived from distinct lineages. Chalermwong et al [ 73 ] asserted that a species complex was identified within the North African catfish, which was characterized by substantial intraspecific sequence divergence, although it was classified under the same species using a species delimitation approach based on DNA barcodes. Moreover, ZZ/ZW sex determination system, which is likely the ancestral system for the North African catfish, is the same as the systems reported in Africa and Israel.…”
Section: Discussionmentioning
confidence: 99%